Analiza i synteza systemu kanałów dystrybucji w ujęciu grafów przepływu sygnałów - Szromnik, Andrzej (Wydział Prawa i Administracji UAM, 1978)
The article deals with modelling as well as with an analysis of a system of commodity distribution channels when graphs of signals flows utilized. On the analogy of information transmission with the aid of communication channels a process of circulation of goods in production and turnover as well as in the sphere of consumption is considered as certain closed entirety, which is mutually conditioned. A simplified reflection of reality is created by a graph of commodity flow, in which curves present a physical circulation of commodities between economic subjects, and internal loops (feedbacks) are reflections of collecting commodities in a given element. Together with the very construction of a graph and its formal description, an attempt has been undertaken to reduce some elements in order to determine resultant capacity of the whole distribution system (the Mason's method) as well as of its particular channels. Such approach to the synthesis of a distribution channels system enables an appraisal of its functioning in definite time with the aid of the "output : input" relation, i.e. the relation "retail sales : production".
Analysis and Synthesis of a System of Distribution Channels with the Aid of Graphs of Signal Flows